Meat quality of veal: Discriminatory ability of weaning status - Pateiro, M.; Lorenzo, J. M.; Diaz, S.; Gende, J. A.; Fernandez, M.; Gonzalez, J.; Garcia, L.; Rial, F. J.; Franco, D. (Spanish Journal of Agricultural Research, 2013)
The physicochemical and fatty acid compositions of meat from 81 calves were measured in order to prove whether the extension of suckling period could distinguish “Normal” from “Suprema” class calves. Three groups of animals were investigated depending on their weaning status: NW (animals were milk-fed until seven months), W1 and W2 (animals which were weaned at different ages and reared either in family farms or in feedlot, respectively). There was no difference among animals in relation to the main components (moisture, protein and ash). Significant differences (p<0.05) were found regarding intramuscular fat; the contents were higher in animals weaned at early ages. Color and texture parameters were significantly affected by weaning status. The intramuscular fatty acid composition in the three types of animals showed that saturated fatty acids were the predominant ones in the three groups with values ranging between 48.71% and 49.52% of total methyl esters. Significant differences (p<0.001) were found depending on weaning status in linolenic acid and in the n-6/n-3 ratio, obtaining the highest values in NW animals. Factor analysis method using principal component was applied to the data. The data matrix constructed was subjected to a canonical discriminant analysis in order to classify the NW, W1 and W2 groups. These results showed that 96.6% for the NW group, and 66.7% and 82.4% for W1 and W2 groups respectively, were correctly classified.